A Descriptive Analysis of Implementing Basic Culinary Principles in Teaching the Main Course Topic of Continental Cuisine at SMK Negeri 6 Padang - Yori Raudhatil Jannah; Juliana Siregar; Wiwik Gusnita; Wiwik Indrayeni (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study aims to examine the implementation of Basic Culinary subjects to improve students’ skills in preparing continental main courses at SMK Negeri 6 Padang. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research informants are teachers who teach continental cuisine subjects. The learning process at the school follows industry standards from the implementation to the evaluation of practical activities. The implementation of Basic Culinary is carried out through integrated theoretical and practical learning, emphasizing mastery of basic cooking techniques, ingredient knowledge, equipment usage, as well as understanding hygiene and sanitation. The teaching methods applied include direct demonstration, the use of interactive media, and question-and-answer sessions to strengthen students’ understanding. Practical sessions are conducted in accordance with industry Standard Operating Procedures (SOP), and quality control is strictly applied from the selection of raw materials to the final product inspection. The role of teachers is crucial in guiding, directing, and evaluating each stage of students’ practical work. Evaluation is conducted comprehensively, covering aspects of planning, implementation, cooking techniques, taste, texture, dish quality, attitude, teamwork, and presentation. The results show that the implementation of Basic Culinary subjects has a positive impact on improving students’ abilities in preparing main courses, both in technical skills and theoretical understanding. Students provide positive feedback on learning based on direct practice and feel better prepared to meet industry demands. Follow-up evaluations include providing opportunities for improvement and discussions among teachers to address challenges encountered during practice. This study recommends that schools and educators continue to enhance the quality of learning based on industry standards to produce competent and job-ready graduates.